Household secondhand smoke exposure and its influencing factors among pregnant women in the Pudong New Area of Shanghai, 2024: a cross-sectional survey - Ling HUANG; Lei GUO; Mengyuan DING; Qian WU; Jiangyu XIAO; Yuxin JIANG; De CHEN; Siyu YU (Zhongguo gonggong weisheng)
ObjectiveTo investigate the prevalence and influencing factors of household secondhand smoke (SHS) exposure among urban and rural pregnant women in Pudong New Area, Shanghai, and to provide evidence for developing targeted smoking control and intervention strategies. MethodsA self-administered voluntary survey was conducted among 11 298 pregnant women who attended early pregnancy registration (first trimester) from January to June 2024 at 47 community health service centers in Pudong New Area, Shanghai. A self-developed questionnaire was used to collect information on participants′ socio-demographics, awareness of SHS-related health hazards, and SHS exposure at home. A multivariable logistic regression model was used to analyze factors influencing household SHS exposure among pregnant women in urban and rural areas. ResultsOf the 11 141 valid respondents (98.6% of all respondents), 14.9% reported exposure to SHS at home in the past 30 days, and exposure was reported by 18.8% of pregnant women in suburban areas, 14.8% in rural-urban areas, and 12.1% in urban areas. Regarding awareness of SHS-related health risks, awareness of SHS-related adult heart disease was the lowest among all groups (67.1%), with urban pregnant women showing a higher awareness rate compared to the other two groups. Stepwise regression analysis identified the following statistically significant predictors of household SHS exposure: for urban pregnant women: husband smoking (odds ratio [OR] = 12.326), cohabitant smoking (OR = 10.822), and no smoking at home (OR = 5.229); for urban-rural pregnant women: husband smoking (OR = 8.809), cohabitant smoking (OR = 3.189), no smoking at home (OR = 5.674), education level (master′s degree or higher, OR = 0.608), awareness of SHS-related heart disease in adults (OR = 0.733), and awareness of lung cancer in adults (OR = 0.612); and for suburban pregnant women: husband smoking (OR = 6.562), cohabitant smoking (OR = 4.510), no smoking at home (OR = 8.266), visitors offering cigarettes (OR = 2.056), age (30 - 34 years, OR = 0.581; ≥ 35 years, OR = 0.521), and awareness of SHS-related lung disease in children (OR = 0.627). ConclusionsHousehold SHS exposure among pregnant women in Pudong New Area cannot be ignored. The influencing factors of household SHS exposure differ between urban and rural pregnant women, suggesting that regional characteristics and awareness of the health hazards associated with household SHS exposure should be fully considered when formulating family tobacco control intervention strategies.